Selective intercalation of chlorophenoxyacetates into the layered double hydroxide [LiAl2(OH)(6)]Cl center dot xH(2)O - Ragavan, A; Khan, A; O'Hare, D (2006)
Chlorophenoxyacetic acids are a well known family of herbicides. 4-Chlorophenoxyacetate (4-CPA), 2,4-dichlorophenoxyacetic (2,4-D), 2,4,5-trichlorophenoxyacetate, (2,4,5-T) have been intercalated into [LiAl 2(OH)6]Cl·xH2O LDH ([Li-Al-Cl] LDH) by ion-exchange. The kinetics and mechanisms involved in the intercalation of each chlorophenoxyacetate have been studied by time-resolved in-situ energy dispersive X-ray powder diffraction (EDXRD). The kinetic preferential order of the intercalation of these herbicides into [Li-Al-Cl] LDH is found to be 4-CPA > 2,4-D > 2,4,5-T. In contrast, thermodynamic guest preference, as determined by performing competitive intercalation reactions is 2,4-D > 4-CPA > 2,4,5-T. The results indicate chlorophenoxyacetate-LDH compounds could have application for the purification, storage and release of chlorophenoxyacetic acid-based agrochemicals. © The Royal Society of Chemistry 2006.